Penguatan UMKM Melalui Digitalisasi dan Pendampingan Legalitas: Sebuah Bentuk Pengabdian Mahasiswa di Desa Sukahening - Astuti, Dewi Ratnasari; Maharani, Mutia; Maulah, Siti; Azizah, Siti Hilma; Maulidiyah, Wuslah Raia; Awwaludin, Rizky Barkatul; Mulyana, Ijang; Haq, Ikmal Syabanul (Rahmah : Jurnal Pengabdian Masyarakat, 2025)
This community service activity aims to empower Micro, Small, and Medium Enterprises (MSMEs) in Sukahening Village through digitalization and business legality assistance. The methods used include digital marketing outreach and training, rebranding in the form of logo, banner, and product catalog creation, and business profile creation on Google Maps. The results of the community service demonstrate an increase in the capacity of MSMEs in managing their businesses digitally and meeting legal requirements, which contributes to increased competitiveness and business development opportunities. In conclusion, this community service supports MSMEs in upgrading and sustainable business development through innovation and strengthening legal aspects. This program emphasizes the strategic role of mentoring and collaboration in strengthening the local economy.